2023
DOI: 10.37934/araset.31.1.4449
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Micronutrients of Purple Sweet Potato Flour as Material Raw Complementary Feeding

Abstract: Safe food is supported by the use of local natural ingredients for food making raw materials. Infants older than 6 months should be given complementary feeding (MP-ASI) for optimal growth. Complementary Feeding in the dominant market is made from wheat flour and tapioca flour, new innovations are needed as a substitute for flour or tapioca, in order to obtain products with high nutritional value. Sweet potato is one of the local confectionary commodities that is safe to be given to babies after 6 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Previous research showed that a significant percentage of carbohydrates, precisely 80%, exhibited a low glycaemic index when PSP was the predominant macronutrient. Additional macroand micronutrients included protein (6.05%), fat (0.76%), iron (6.7049 mg/kg), and zinc (8.5595 mg/kg), as reported by Fitri et al (2023) and Legi et al, (2023). Sweet potato flour primarily consists of carbohydrates, rendering it a viable and efficient energy source.…”
Section: Samplementioning
confidence: 76%
“…Previous research showed that a significant percentage of carbohydrates, precisely 80%, exhibited a low glycaemic index when PSP was the predominant macronutrient. Additional macroand micronutrients included protein (6.05%), fat (0.76%), iron (6.7049 mg/kg), and zinc (8.5595 mg/kg), as reported by Fitri et al (2023) and Legi et al, (2023). Sweet potato flour primarily consists of carbohydrates, rendering it a viable and efficient energy source.…”
Section: Samplementioning
confidence: 76%